A NIR luminescent copolymer based on platinum porphyrin as high permeable dissolved oxygen sensor for microbioreactors. Issue 8 (22nd March 2013) - Jin, Pengwei; Chu, Ju; Miao, Yu; Tan, Jun; Zhang, Siliang; Zhu, Weihong
Abstract : Microbioreactors with multioptical sensors have become increasingly important because of their small working volumes, high degree of parallelization and the available robotics. A novel hydrophobic luminescent copolymer P(Pt‐TPP‐TFEMA) along with reference P(Pt‐TPP‐EMA) containing the pendant group of 5, 10, 15, 20‐tetraphenylporphyrin (TPP) moiety as low‐cost dissolved oxygen (DO) chemosensor film for high‐throughput microbioreactors is designed. Its sensor film exhibits fast response to DO with good stability and fatigue resistance, being capable of applying as a low‐cost DO indicator for high‐throughput bioprocess measurement. Results show that the quenching response of DO increases with the enhancement in the copolymeric hydrophobicity using the presented hybrid fluorinated ethyl methacrylate. Furthermore, the long emission band at 650 nm of chromophore TPP with large Stoke's shift about 250 nm brings several advantages, such as low scattering, deep penetration, and minimal interferences of absorption and fluorescence from the fermentation system, which shows high‐promising application in bioprocess monitoring. © 2013 American Institute of Chemical Engineers AIChE J, 59: 2743–2752, 2013